Determinants of Interest in the Use of Islamic Digital Wallets - Mawadah, Zahrotul; Darwanto, Darwanto (EQUILIBRIUM, 2023)
This study aims to determine the effect of variables perceived ease of use (X1), perceived usefulness (X2), perceived risk (X3), perceived security (X4), and trust (X5) on student interest in using LinkAja Syariah services by using an approach The Theory Acceptance Model (TAM). The data used are primary data by using the method of distributing questionnaires via google-form. The technique used in this research is using purposive sampling. The number of respondents obtained in this study was 280 respondents. The analytical technique used in this study uses the Structural Equation Model Partial Least Square (SEM-PLS) method. The results of this study indicate that perceived ease of use, perceived risk, perceived security, and trust have a positive and significant effect on student interest in using LinkAja Syariah services. While the perceived usefulness variable does not affect student interest in using the LinkAja Syariah service.  This study implies that this study can be an input for business leaders, especially those involved in electronic payment services, to pay attention to the perceived interest, usefulness and usefulness, perceived benefits, perceived risks, security, and confidence in improving the quality of e-services portfolio services. Based on the results of this study, perceived usefulness may not affect preference to use LinkAja Syariah, so other variables should be included in further research.